Literature study on effects of music to the udatholiliyal function of the yakkai in siddha aspects - Sivalathajini, V.; Sounthararajan, K.; Nirosh, R. (3rd International Conference on Ayurveda, Unani, Siddha and Traditional Medicine 2015, 2015)
Music is an art form which has not only been influencing the world but has also taken the role of a universal language that is understood by every human being. Music has the capability to appeal towards the emotions and beliefs of human beings. Music is a powerful force which taps a person's personal identity, memories and mood. The objective of this study Research in music therapy supports its effectiveness in many areas such as overall physical rehabilitation and facilitating movement increasing people's motivation to become engaged in their treatment, providing emotional support for clients and their families and providing an outlet for expression of feelings. In this study mentioned the Ragas related to the diseases, how music therapy work, chakras and related glands, music profound effect on body and mind, Raga and its effects. Physiological function is the science of the mechanical, physical, and bio chemical function. As a discipline, it connects science, medicine, health and creates a framework for understanding how the human body adapts to stresses, physical activity and disease. Listening to each kinds of music at specific times of the day has been shown to be helpful in maintaining good physical and mental health. Music with its many Ragas' is known to be particularly for its therapeutically value. The curative power of music emanates from the resonance of certain 'Ragas' on hormonal and glandular function which produce secretions that keep the body balanced and free of infection. Music on body and mind and put in to practice the vibrations emanating from sounds to uplift one's level of consciousness. That recognized that Ragas are not just mere commodities of entertainment but the vibrations in their resonance could synchronize with one's moods and health. By stimulating the moods and controlling the brain wave patterns, Ragas could work as a complementary medicine.
Keywords: Music therapy; Physiological function; Siddha aspects; Physical; Emotional